BUILD A WEB-BASED SALES APP ON HOKKY PETSHOP - I Made Kusuma Dicky yuliawan; M.J Dewiyani Sunarto; Januar Wibowo (Jurnal Sistem Informasi Universitas Dinamika, 2022)
Hokky Petshop is a place of business engaged in the sale of pet food and accessories. Hokky Petshop is located on Jalan Kebo Iwa Utara number 12 Denpasar, Bali. Hokky Petshop sells products in the form of food and animal accessories. So far, marketing has been done through existing social media. The problem faced is that the sales department has difficulty if the goods that are of interest to customers are not found, because the sales department must find the amount of inventory in the inventory book. This results in the customer having to wait for five (5) minutes. Another problem is that the sales department has difficulty in making monthly reports because sales notes are often tucked away. This results in a mismatch of sales reports with records of goods that come out each month. The next problem is that so far the reports submitted to the owners are only limited to monthly sales reports, so the owners have to calculate their own comparison of the number of monthly sales and sort out which food products are the best-selling. Based on these problems, an application for selling food and animal accessories was made that can solve problems at Hokky Petshop. The application is made web-based because the owner can view sales reports in real-time and can help the petshop to record sales transactions stored in the system, display sales comparisons each month and can find out which products are the bestsellers. Based on the test results, the application that has been made can be used by store owners in managing sales data, and goods data. Store owners can also find out which products have the highest and lowest sales and create product sales reports, which can be used to search for monthly sales reports. There are notifications regarding remaining stock, product expiration periods and also comparison charts that can help shop owners find out the comparison of product sales from the previous month. Keywords: Hokky Petshop, Sales Application, Website